Controlled‐release drug carriers based hierarchical silica microtubes templated from cellulose acetate nanofibers. Issue 38 (17th June 2015) - Jia, Chengying; Song, Junlong; Jin, Yongcan; Rojas, Orlando J.
ABSTRACT We report a facile method to synthesize hollow silica microtubes (SMTs) from electrospun cellulose acetate fiber precursors. Specific surface areas of up to 765 m2/g (Brunauer–Emmett–Teller) were measured for the SMTs, which had a typical wall thickness of ∼100 nm and submicron inner diameters. An average pore size of 4.6 nm and pore volume of 0.41 cm3/g were derived from Barrett–Joyner–Halenda fitting, whereas Horvath–Kawazoe pore size distribution analysis revealed microporous median pore size and maximum pore volume of 0.7 nm and 0.18 cm3/g, respectively. The as‐prepared SMTs featuring micro‐ and mesoporous structures in the walls where amino‐functionalized to facilitate a very high drug loading (15% by weight). Drug release profile revealed sustained release rates (79% of acetylsalicylic acid was released after 6 h). It is concluded that the high drug loading and sustained release resulted from the advantageous integration of SMTs' hollow structure and wall mesoporosity. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42562.